2016
DOI: 10.15740/has/ijas/12.2/241-244
|View full text |Cite
|
Sign up to set email alerts
|

Studies on seed quality parameters in Indian mustard [Brassica juncea (L.) Czern and Coss]

Abstract: An evaluation of thirty two accessions of Indian mustard [Brassica juncea (L.) Czern and Coss] was carried out during 2014-2015 in Completely Randomized Design (CRD) with three replications in Laboratory revealed highly significant differences among the accessions for all seed vigour traits. Observations were recorded on ten seed vigour traits viz.,1000-seed weight (g), field emergence (%), speed of germination (at field), germination, speed of germination, root length (cm), shoot length (cm), seedling length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…A close proximity in PCV and GCV was observed in plant height, height up to first fruiting branch, days to 50% flowering, days to physiological maturity and siliquae per plant in both the generations except siliquae per plant in F 3 generation indicating little influence of the environment in the expression of these yield attributing characters studied. Similar results were obtained by Singh et al, (2015) and Srivastava et al, (2016).…”
Section: Resultssupporting
confidence: 91%
“…A close proximity in PCV and GCV was observed in plant height, height up to first fruiting branch, days to 50% flowering, days to physiological maturity and siliquae per plant in both the generations except siliquae per plant in F 3 generation indicating little influence of the environment in the expression of these yield attributing characters studied. Similar results were obtained by Singh et al, (2015) and Srivastava et al, (2016).…”
Section: Resultssupporting
confidence: 91%
“…This showed that there was least influence of environment in the expression of traits. High GCV and PCV were earlier reported Srivastava et al [14] and Rauf and Rahim [13].…”
Section: Coefficient Of Variationsupporting
confidence: 53%
“…A number of research workers have observed increases in these attributes in mustard crop viz. Sahoo et al (2018) and Singh et al (2014).…”
Section: Dry Weight Of Plantmentioning
confidence: 99%
“…The lowest cost of cultivation in T 1 (100% RDF (60 kg N, 30 kg P 2 O 5 /ha)) treatment was attributed to the low cost of chemical fertilizers (urea, single superphoshate), as well as the fact that there were applied in a small quantities chemical fertilizers used in comparison to organic manures. As a result, the labour and transportation costs were declined (Singh et al (2014)). The gross returns were significantly greater with T 4 .…”
Section: Economics Of Mustard Cropmentioning
confidence: 99%
See 1 more Smart Citation